EFFECT OF TWO NEWLY SYNTHESIZED RIBOFURANOSE DERIVATIVES ON THE PLASMA XANTHINE OXIDASE ACTIVITY IN PATIENTS WITH CHRONIC RENAL FAILURE (Academicia Globe: Inderscience Research, 2023)
Renal failure claims the lives of humans worldwide. Several studies suggest that oxidative stress is a major factor in deterioration of renal function. Oxidative stress seems to play a pivotal role in this process, and purine metabolism may be involved in renal failure-related oxidative stress. Xanthine oxidase is an enzyme involved in purine metabolism and is also responsible for producing reactive oxygen species.